2021
DOI: 10.4102/sajhivmed.v22i1.1220
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus and mortality from coronavirus disease 2019: A systematic review and meta-analysis

Abstract: Background: Persons living with human immunodeficiency virus (PLWH) constitute a vulnerable population in view of their impaired immune status. At this time, the full interaction between HIV and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been incompletely described.Objective: The purpose of this study was to explore the impact of HIV and SARS-CoV-2 co-infection on mortality.Method: We systematically searched PubMed and the Europe PMC databases up to 19 January 2021, using specific keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 58 publications
1
31
1
Order By: Relevance
“…contribute to the development of severe form of Covid-19, causing further inflammation and immune dysfunction that leads to the formation of cytokines storm which is life threatening. [2][3][4][5][6][7] Several therapies had been proposed to control and manage these conditions. [8][9][10][11][12][13][14] Recently the use of GLP1-RA, as one alternative to treat DM patients, had shown promising effect to reduce excessive inflammation-induced acute lung injury and improving Covid-19 outcome.…”
Section: Introductionmentioning
confidence: 99%
“…contribute to the development of severe form of Covid-19, causing further inflammation and immune dysfunction that leads to the formation of cytokines storm which is life threatening. [2][3][4][5][6][7] Several therapies had been proposed to control and manage these conditions. [8][9][10][11][12][13][14] Recently the use of GLP1-RA, as one alternative to treat DM patients, had shown promising effect to reduce excessive inflammation-induced acute lung injury and improving Covid-19 outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with comorbidities such as obesity, diabetes, chronic respiratory disease, cardiovascular disease and other immunocompromising conditions are facing higher risks in developing the severe form of SARS‐CoV‐2 infections. 4 , 5 , 6 , 7 , 8 , 9 For the past months, medical therapies to treat Covid‐19 have been growing and evolving rapidly, ranging from supportive care, antivirals, anti‐inflammatory agents and possible supplementations such as vitamin D. 10 , 11 , 12 , 13 Several studies have shown that vitamin D has antiviral properties and potential roles against acute lung injury or ARDS, making large interest on vitamin D has rapidly emanated even in the early beginning of pandemic. 14 , 15 Low vitamin D serum levels is associated with an increase in inflammatory cytokine levels and significant increase of risk to develop pneumonia and viral respiratory tract infections, which both contribute to the development of ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…92 Two systematic reviews/meta-analyses also concluded that PWH had a higher risk of mortality, though only in studies of PWH from Africa and the United States. 93 , 94 A smaller study of PWH in Brazil ( n = 255) found that being Black/Mixed race and having lower education were associated with greater mortality in adjusted models, while age, sex, CD4 count, viral load, and comorbidities were not. 63 To the best of our knowledge, thus far only one study has investigated the risk of post-acute symptoms following COVID-19 and found that moderate to severe disease was associated with an increased risk of persistent symptoms in PWH.…”
Section: Discussionmentioning
confidence: 99%